2017
DOI: 10.1097/gco.0000000000000407
|View full text |Cite
|
Sign up to set email alerts
|

To image or not in noncyclic breast pain? A systematic review

Abstract: There is a low prevalence of breast cancer in patients with painful breast with negative physical examination, and very little research to inform about the effect of performing or avoiding initial imaging test on outcomes of interest. With such limited evidence, only a weak recommendation to reinforce shared decision making about what should be done in the primary care setting can be made, with the backup of a specialized breast unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Rates of breast cancer in women with mastalgia alone, in the absence of other breast symptoms, range from 0% to 0.4%. 17 19 These data are similar to cancer detection rates in asymptomatic women within the NHS breast screening programme 20 and suggest that any diagnosis of breast cancer accompanying the presence of mastalgia in a woman with no other breast symptoms is likely a coincidental occurrence.…”
Section: Discussionsupporting
confidence: 63%
“…Rates of breast cancer in women with mastalgia alone, in the absence of other breast symptoms, range from 0% to 0.4%. 17 19 These data are similar to cancer detection rates in asymptomatic women within the NHS breast screening programme 20 and suggest that any diagnosis of breast cancer accompanying the presence of mastalgia in a woman with no other breast symptoms is likely a coincidental occurrence.…”
Section: Discussionsupporting
confidence: 63%
“…Seventy per cent of women (85/121) were satisfied with their outcome, reporting lack of progression or resolution of symptoms. A recent systematic review concluded that primary care can be a good location for managing women with breast pain, including assessment of breast cancer risk, provided that healthcare professionals in primary care are supported with well-defined protocols and easy access to secondary care for clinical advice 10 . Such protocols have been adopted successfully for assessing cardiovascular risk in primary care 31 and more work is needed to develop and assess similar protocols for breast cancer risk assessment in women with breast pain alone.…”
Section: Discussionmentioning
confidence: 99%
“…These largely have been smaller retrospective cohorts, unclear on the separate analysis of women with breast pain alone or with associated other breast symptoms. A systematic review of the breast pain literature found the quality of evidence relating to breast pain diagnosis and management to be poor 10 . Seven of 8 studies in the past 10 years note rates of 0-0.4% 8 with the small numbers of malignancies seen being in women above 40 years 12 25 37 .…”
Section: Comparison With Existing Literaturementioning
confidence: 99%